1996
DOI: 10.1116/1.589154
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam induced deposition from W(CO)6 at 2 to 20 keV and its applications

Abstract: Formation of submicron oxide widths on aluminum in the presence of keV electron beams and CO2 or N2O J. Vac. Sci. Technol. A 4, 241 (1986); 10.1116/1.573435Electron beam lithography from 20 to 120 keV with a high quality beam Electron beam induced deposition from W͑CO͒ 6 was studied for beam energies between 2 and 20 keV and a range of exposure doses, to investigate the dependence of deposit thickness and electrical conductivity on energy and the dependence of deposit conductance on cumulative exposure dose. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 8 publications
3
77
2
Order By: Relevance
“…Tungsten hexacarbonyl (W(CO) 6 ) powder was used as a precursor, of which the vapor pressure is approximately 2 Pa at room temperature. The precursor has been proved to be suitable for fabricating nano-sized structures on conductive substrates 1,3,5,7) as well as on insulator substrates 9,10) with EBID. Crystalline SiO 2 thinfilm specimens suitable for TEM observation were used as substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten hexacarbonyl (W(CO) 6 ) powder was used as a precursor, of which the vapor pressure is approximately 2 Pa at room temperature. The precursor has been proved to be suitable for fabricating nano-sized structures on conductive substrates 1,3,5,7) as well as on insulator substrates 9,10) with EBID. Crystalline SiO 2 thinfilm specimens suitable for TEM observation were used as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the controllability of the beam, zero, one, two, or three dimensional small-sized objects have been fabricated. [1][2][3][4][5][6][7][8] Conductive substrates are generally used in these fabrications, because they provide stable fabrication conditions. Recently, by using insulator substrates, Al 2 O 3 , nanometer-sized (nano-sized) tungstenstructures (W-structures), namely, wire-like, dendrite-like and tree-like W-structures, have been fabricated with EBID using a precursor W(CO) 6 in a 200 kV transmission electron microscope.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to measure deposition yields ͑the amount of material deposited per electron͒, but a measurement of tot requires an estimate of the steady state coverage of precursor molecules on the surface. Total reaction cross sections have been estimated in this way; for example by Scheuer and Koops 8 ͑who found a value of 2 ϫ 10 −17 cm 2 at an energy of 40 keV for Ru 3 ͑CO͒ 12 ͒ and Hoyle et al 9 ͓who observed values in the order of 0.5-1.5 ϫ 10 −18 cm 2 for W͑CO͒ 6 at incident electron energies between 2 and 20 keV͔.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In situ techniques focus mainly on changing the electron beam parameters, namely, the spot size, dwell time, or current density. [8][9][10][11][12] Another in situ approach to improve purity has involved performing EBID on a heated substrate. 8 For example, using the Me 2 Au(tfac) precursor Koops et al showed that depositions carried out at a substrate temperature of 80 C resulted in EBID materials with lower resistivity compared to deposits created on substrates maintained at room temperature.…”
Section: Introductionmentioning
confidence: 99%